Unveiling the Bioactive Potential: Phytochemical Profiling and Biological Activities of Syzygium nervosum Bark - Khanal, Lekha Nath; Neupane, Sujan; Dhakal, Purna Prasad; Kandel, Mani Ram (Amrit Research Journal, 2025)
Since ancient times, plant-based remedies have played a vital role in managing health complications. This study investigates the phytochemical composition, antioxidant, and antibacterial potential of diverse solvent extracts of Syzygium nervosum collected from the Kaski district of Nepal. Among the tested fractions, the dichloromethane extract showed the highest phenolics (81.15 ± 0.02 mg GAE/g), followed by hexane (78.79 ± 0.10 mg GAE/g), ethyl acetate (72.00 ± 0.08 mg GAE/g), and aqueous fractions (19.25 ± 0.02 mg GAE/g). In contrast, the hexane extract showed the highest flavonoid content (233.54 ± 1.00 mg QE/g), followed by dichloromethane (219.54 ± 0.60 mg QE/g), ethyl acetate (156.94 ± 0.53 mg QE/g), and methanol (141.94 ± 0.92 mg QE/g). Antibacterial screening by agar well diffusion revealed that the ethyl acetate fraction showed moderate activity against Escherichia coli (14.0 mm), Staphylococcus aureus (13.0 mm), and Pseudomonas aeruginosa (9.0 mm). Antioxidant activity, determined by DPPH assay, was highest for ethyl acetate (IC50 = 27.92 µg/mL), followed by dichloromethane, hexane, methanol, and aqueous fractions. The aqueous extract exhibited the weakest activity. Overall, Syzygium nervosum demonstrates promising bioactive potential, supporting its future application in developing therapeutic agents against oxidative stress and microbial infections.